Study on Oil Production from Black Soldier Fly (Hermetia illucens) Maggots as a Feed Additive for Broiler - Maulana, Maulana; Montesqrit, Montesqrit; Mirzah, Mirzah (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2025)
The broiler chicken farming industry in Indonesia continues to experience rapid growth in line with the increasing demand for chicken meat. To support the development of this industry, one of the main challenges that must be addressed is the availability, efficiency, and quality of feed. The aim of this study was to determine the effect of Black Soldier Fly (Hermetia illucens) maggot oil as a feed additive on the performance, abdominal fat, and intestinal E. coli of broiler chickens. This research was conducted experimentally using a completely randomized design (CRD) with 5 treatments and 4 replications. Each experimental unit consisted of 5 MB-212 P broiler chickens from PT. Japfa, with the following treatment details: R0 – 0% maggot oil in the feed; R1 – 0.5% maggot oil (14-day-old) in the feed; R2 – 1% maggot oil (14-day-old) in the feed; R3 – 0.5% maggot oil (28-day-old) in the feed; and R4 – 1% maggot oil (28-day-old) in the feed. Results of the Duncan’s Multiple Range Test showed that all measured parameters, except for abdominal fat, were significantly affected (P<0.05) by the supplementation of maggot oil in the feed. The addition of 1% maggot oil from 14-day-old larvae as a feed additive significantly improved broiler performance, as indicated by the highest feed intake of 352.28 g/bird, live weight of 1,058.5 g, carcass percentage of 83.44%, abdominal fat of 1.47%, and intestinal E. coli count of 4.00 × 10⁵ CFU/g.However, the supplementation of 1% maggot oil from 28-day-old larvae resulted in poorer broiler performance, as indicated by lower feed intake (286.90 g/bird) and a relatively high feed conversion ratio (FCR) of 2.03.